Protection of registered proprietor in Malaysia: with special reference to fraud and forgery cases on land title registration / Ag. Danam @ Ag. Adnan Pg Bakar - Pg Bakar, Ag. Danam @ Ag. Adnan (2017)
This research concerned on the National Land Code 1965. The rights of registered proprietor if losing their land through fraud and forgery. The land fraud statistics in Malaysia's administration system shows that legal security, at present, is not able to guarantee registered proprietor in the long run. Furthermore there are registered landowners who are not able to recover their losses due to the stripping of title done erroneously by the government. This occurs due to the Malaysia's administration system only practices two principles out of three principles in the Torrens system, which is the mirror principle and the curtain principle. This has revealed the failure of the government in guaranteeing the landowner in the form of economic security. As an overall result, it is to recommend the authority or the land administrator adopting the third principle of Torrens system which is guarantee principle.